A robust fuzzy logic PI controller for solar system battery charging - Mohammed Zerouali; Abdelghani El Ougli; Belkassem Tidhaf (Institute of Advanced Engineering and Science, 2023)
This article discusses a design of a photovoltaic (PV) system that allow charging a battery under variable climatic circumstances. The system under study is composed of two DC-DC converters a boost and Buck converter. The first one is used to extract the maximum power from the PV array through a novel variable step size P&O based MPPT offering a high tracking accuracy compared to classical approaches such PO and INC. The second converters aim at regulating the output voltage and current that feeds the battery using a robust optimal PI (O-PI) which has a faster time response and high accuracy compared to classical PI and PID controllers. The overall system and thecontrol strategies are tested and validated in MATLAB/Simulink environment. The simulations results show the effectiveness and the robustness of the system.